Desenvolvimento da fé e educação cristã na infância para a formação cidadã da criança - Pimentel, Jéferson Polidoro Ruaro (2014)
This dissertation presents information about how faith arises, how its expression occurs in relation with the sacred, and in which way it develops in the first years of human life. Empashis is placed on the life stage considered childhood in current society. With this approach, the research seeks to identify if the Christian education, oriented by the principles of Jesus' Gospel, features in its base information capable of leading a child to a citizen life. With a philosophical view, the moral and ethics were studied as relevant features, which challenge the human being to citizenship and to a good social co-existence inside the group to which he belongs. The hypothesis defended here understands that Christian education, if used as a pedagogic method and interpreted in an adequate form, when implemented by those who suggest its dissemination, may lead the child to an ethical life focused on the wisdom of love.